2019
DOI: 10.7224/1537-2073.2017-090
|View full text |Cite
|
Sign up to set email alerts
|

Research-to-Practice Gaps in Multiple Sclerosis Care for Patients with Subjective Cognitive, Mental Health, and Psychosocial Concerns in a Canadian Center

Abstract: Background: People with multiple sclerosis (MS) are at increased risk for cognitive impairment, mental health concerns, and psychosocial issues, which can negatively affect disease outcomes and quality of life. Current MS care guidelines recommend integrated interdisciplinary services to address these concerns; however, issues can be overlooked during routine care. To date, there is inadequate research on how often these issues are identified and addressed during routine MS care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that rates of identification of cognitive concerns in standard clinical practice are significantly lower than the identified prevalence in epidemiologic studies. This has been attributed to overreliance on selfdisclosure by PwMS and HCP's concerns about broaching cognition when they feel that inadequate resources are available to address these issues (Walker et al, 2019).…”
Section: (Ii) Communicationmentioning
confidence: 99%
“…It has been demonstrated that rates of identification of cognitive concerns in standard clinical practice are significantly lower than the identified prevalence in epidemiologic studies. This has been attributed to overreliance on selfdisclosure by PwMS and HCP's concerns about broaching cognition when they feel that inadequate resources are available to address these issues (Walker et al, 2019).…”
Section: (Ii) Communicationmentioning
confidence: 99%
“…We anticipate that respondents will identify several areas of unmet need, particularly as they relate to treatments for fatigue, mood, and cognitive challenges. Our own group has identified a significant gap between the research progress in these areas and the services available to address these issues in standard clinical practice ( 75 ). While exercise interventions may be more readily available in the community at large, there continue to be environmental barriers to accessibility ( 76 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment remains a neglected and under-diagnosed symptom of MS. The “invisibility” of cognitive difficulties has meant they are often overlooked by family members, colleagues and healthcare professionals since there is no obvious external disability [ 19 ]. At routine consultation, neurologists are poor at identifying MS-related cognitive impairment [ 20 ].…”
Section: Introductionmentioning
confidence: 99%